EFFECT OF TEACHER (FACILITATOR) VARIABLES ON MEETING DISTANCE LEARNERS’ EDUCATIONAL AND SOCIAL NEEDS - A., Adegbile J.; O., Oyekanmi J. (Sokoto Educational Review, 2020)
The effect of the teacher as the facilitator of learning behaviour in any distance learning mode cannot be overemphasized. As the carrier and transmitter of knowledge, his characteristic variable and delivery media are very important as no technology application can successfully be in use without the active impact of the teacher (facilitator) otherwise, the implementation of distance education stands the risk of becoming a dismal failure. The study therefore, identified the effect of teacher (facilitator) variables on meeting the educational and social needs of distance learners in the University of Ibadan .Stratified and sampling according to proportional size techniques were used to sample 65 distance learners’ facilitators from the 5 faculties of the University - Education, Arts, the Social Science, Science, and Agriculture and Forestry participating in the programme for this study. Two research questions were posed for the study. Distance Learners’ Facilitators Questionnaire (DLFQ) with reliability coefficient of 0.70 was utilized for data collection, using Multiple Regression to analyse the data collected. The study found that the facilitator variables recanted empirical studies on the effect of facilitator variables on learner’s needs. However, it replete the facts that the effect of facilitator variables could not be undermined, though they could be lessened through adequate use of technologies on the basis of the findings; facilities needed by facilitators should be provided to enhance belter performance.